A review of psychosocial and psychological and its related issues in the occupational settings - Nuruzzakiyah, Mohd Ishanuddin; Ezrin Hani, Sukadarin; Hanida, Abdul Aziz (Universiti Malaysia Pahang, 2018)
Psychosocial risk and psychological risk were different from each other although they were associated to the term of mental health. Both are related to a condition of a person mental health that they are not physically visible specifically in the workplace. The study regarding mental health at the workplace has been conducted long time ago by many researchers, thus psychosocial and psychological issues in the workplace were quite familiar due to the emergence of new types of hazards and associated risks in the workplace settings. In respect to that, no one should be harm by their work nature had driven more studies on these invisible aspects. To avoid more confusion between these terms, proper understanding must be developed in order to use any of these terms in research. This paper draws a clear distinction between these two terms (psychosocial risk and psychological health) and the related issues in the workplace settings.